2018
DOI: 10.1371/journal.pone.0199859
|View full text |Cite
|
Sign up to set email alerts
|

Association of infant formula composition and anthropometry at 4 years: Follow-up of a randomized controlled trial (BeMIM study)

Abstract: The relationships between nutrition, metabolic response, early growth and later body weight have been investigated in human studies. The aim of this follow-up study was to assess the long-term effect of infant feeding on growth and to study whether the infant metabolome at the age of 4 months might predict anthropometry at 4 years of age. The Belgrade-Munich infant milk trial (BeMIM) was a randomized controlled trial in which healthy term infants received either a protein-reduced infant formula (1.89 g protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
14
1
2
Order By: Relevance
“…In contrast to the CHOP trial, the BeMIM trial found higher weight-for-length z-scores in infants fed a formula with low protein content (1.89 g/100 kcal) as compared with infants fed 2.2 g/100 kcal protein during the intervention time (up to 120 days), 33 but no difference was observed at age 4 years. 37 However, the range of protein content considered in this trial was lower than in the CHOP trial or in our study. Moreover, the formula with reduced protein content was also enriched in long-chain polyunsaturated fatty acids, so a formal comparison between the two IFs is impossible.…”
Section: Discussioncontrasting
confidence: 65%
“…In contrast to the CHOP trial, the BeMIM trial found higher weight-for-length z-scores in infants fed a formula with low protein content (1.89 g/100 kcal) as compared with infants fed 2.2 g/100 kcal protein during the intervention time (up to 120 days), 33 but no difference was observed at age 4 years. 37 However, the range of protein content considered in this trial was lower than in the CHOP trial or in our study. Moreover, the formula with reduced protein content was also enriched in long-chain polyunsaturated fatty acids, so a formal comparison between the two IFs is impossible.…”
Section: Discussioncontrasting
confidence: 65%
“…Cabe destacar lo observado con proteínas y carbohidratos, los cuales tuvieron una adecuación sobre lo esperado, siendo en las proteínas similar a lo observado en un estudio italiano en niños de 6, 9 y 12 meses 35 , existen diversos estudios que asocian el exceso en la ingesta de estos macronutrientes y obesidad infantil. Esta relación se ha observado en lactantes que consumen fórmulas lácteas (FL) infantiles con alta concentración de proteínas 36,37 y en conjunto con su alimentación complementaria 38,39 , donde se ha visto aumento del peso y grasa corporal. Los resultados concuerdan con un estudio nacional el cual mostró los problemas que existen en la dilución de las FL, siendo más habituales en el NSE bajo, en el que cerca de un 40% de los padres la concentraba por sobre lo recomendado en niños entre 6 a 11 meses 40 .…”
Section: Discussionunclassified
“…Nutrimetabolomics studies using human milk samples have been focused on because, in addition to being non-invasive and easy to collect, fetal and infancy nutritional statuses may affect their subsequent growth, health risk, or genetic modification. In fact, reports included not only studies on changes in perinatal milk composition, but also studies investigating links between maternal obesity and human milk metabolites [40] as well as risks of postnatal weight gain [41].…”
Section: Human Milkmentioning
confidence: 99%